Evidence for the Involvement of Sulfhydryl Oxidation in the Regulation of Fat Cell Hexose Transport by Insulin - Czech, Michael P. (1974)
Previous studies have shown that the oxidants Cu(++), H(2)O(2), and diamide mimic the stimulatory effect of insulin on 3-O-methylglucose transport in isolated fat cells. The present experiments were designed to determine whether sulfhydryl oxidation plays a key role in the activation of the glucose transport system. It was found that reductants such as dithiothreitol inhibited 3-O-methylglucose transport rates and that this effect was reversible when cells were washed free of reducing agent. Treatment of cells with 1 mM N-ethylmalcimide for 5 min completely blocked the actions of insulin and oxidants on hexose transport without affecting control transport system activity. Under these conditions, binding of (125)I-labeled insulin to fat cell surface receptors was inhibited by only about 50%. Addition of insulin or oxidants to fat cells for 10 min before addition of N-ethylmaleimide completely prevented the inhibitory effect of N-ethylmaleimide on the activated transport system. This protective effect on transport rates appears to reside at a site that is altered by insulin subsequent to hormone-receptor interaction, since prior treatment of fat cells with insulin did not prevent the partial inhibitory effect of N-ethylmaleimide on insulin receptors. Furthermore, treatment of cells with N-ethylmaleimide after incubation with insulin prevented the elevated transport rates from returning to control levels when either the cells were washed free of hormone or insulin binding to its receptors was disrupted by trypsin digestion. However, transport rates in these cells treated with N-ethylmaleimide remained sensitive to cytochalasin B, phlorizin, and reductants. These data suggest that a component of the glucose transport system in isolated fat cells must be maintained in its disulfide state for expression of transport activity. Further, the results are consistent with the concept that the binding of insulin to cell surface receptors triggers sulfhydryl oxidation in this component, which prevents its reaction with N-ethylmaleimide.